Impact of high-dose norepinephrine during intra-hospital damage control resuscitation of traumatic haemorrhagic shock: A propensity-score analysis. Issue 5 (May 2020) - Cardinale, M.; Cungi, P.J.; Esnault, P.; Nguyen, C.; Cotte, J.; Montcriol, A.; Prunet, B.; Bordes, J.; Renard, A.; Meaudre, E.
Highlights: Norepinephrine infusion to maintain blood pressure goal during haemorrhagic shock still remains a matter of debate. The European recommendations suggests the use of vasopressors when fluid expansion fails to maintain the blood pressure goal. Important information, such as the dose of vasopressor during haemostasis surgery, has not been described. A maximum norepinephrine infusion rate > 0.6 μg/kg/min is associated with a higher SOFA score at 24 h. Abstract: Introduction: The use of norepinephrine (NE) during uncontrolled haemorrhagic shock (HS) has mostly been investigated in experimental studies. Clinical data including norepinephrine dose and its impact on fluid resuscitation and organ function are scarce. We hypothesized that there is great variability in NE use and that high doses of NE could lead to increased organ dysfunction as measured by the sequential organ failure assessment (SOFA). Method: We included patients with HS (systolic blood pressure < 90 mmHg in severely injured patients) who required haemostasis surgery and a transfusion of more than 4 packed red blood cells (PRBC) in the first 6 h of admission and the used of norepinephrine infusion to maintain the blood pressure goal, between admission and the end of haemostasis surgery in a prospective trauma database. A ROC curve determined that, using Youden's criterion, a dose of NE ≥ 0.6 µg/kg/min was the optimal threshold associated with intrahospital mortality. Patients were compared according to this threshold in a propensity score (PS) model. In a generalized linear mixed model, we searched for independent factors associated with a SOFA ≥ 9 at 24 h Results: A total of 89 patients were analysed. Fluid infusion rate ranged from 1.43 to 57.9 mL/kg/h and norepinephrine infusion rate from 0.1 to 2.8 µg/kg/min. The HDNE group received significantly less fluid than the LDNE group. This dose is associated with a higher SOFA score at 24h: 9 (7–10) vs. 7 (6–9) ( p = 0.003). Factors independently associated with a SOFA score ≥ 9 at 24 h were maximal norepinephrine rate ≥ 0.6 µg/kg/min (OR 6.69, 95% CI 1.82 – 25.54; p = 0.004), non-blood resuscitation volume < 9 mL/kg/h (OR 3.98, 95% CI 1.14 – 13.95; p = 0.031) and lactate at admission ≥ 5 mmol/L (OR 5.27, 95% CI 1.48 – 18.77; p = 0.010) Conclusion: High dose of norepinephrine infusion is associated with deleterious effects as attested by a higher SOFA score at 24 h and likely hypovolemia as measured by reduced non-blood resuscitation volume. We did not find any significant difference in mortality over the long term.